(untitled) (Bangladesh Journal of Livestock Research, 2020)
An attempt was made to study the existing production and management system under intensive buffalo farming at Dinajpur district, a drought area of Bangladesh. Thirty two farmers were selected for this study. Direct interview with farmers, farm observation, community discussions and key informant interview (KII) were carried out to achieve the study. Two types of intensive system were found, namely – household yard (HYI) and completely intensive (CI). It was observed that in HYI system during the day time the animals were kept in yard and in confinement at night. On the contrary, animals were always remained in the shed under CI system. Feeding practice and utilization of feed resources were found different in HYI and CI farming. Showering of dairy buffaloes was observed as common practices in both production systems. All productive e.g. milk yield, lactation yield, lactation length and dry period and reproductive traits e.g. service per conception, age at first pregnancy, age at first calving and post/partum heat period under CI production system were found significantly (p≤0.05) better than that of the HYI systems. Significantly (p≤0.05) higher total solids and fat were found in milk from CI system compared to the HYI system, but in case of protein it was opposite. Natural breeding showed as more prominent practice than that of the artificial insemination in both farming systems. All the farmers practiced colostrum feeding and the calf mortality ranges from 7-8%. Regarding the primary health care, CI farmers were found to be more attentive than the HYI farmers. Most of the buffaloes showed heat from early night to early morning (78.7%). Problem matrix revealed that the top ranked order of problems were “inadequate knowledge”, “high price of feed” and “low milk price”. However, both systems were found as a profitable venture (benefit cost ratio1.33 in HYI and 1.25 in CI). Bangladesh J. of Livestock Res. 21-25: 103-117, 2018